2013
DOI: 10.5897/jetr2013.0306
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and characterization of self compacting concrete with silica fume

Abstract: Self-compacting concrete (SCC) was elaborated using local materials and silica fume (SF) as admixture in 15% of cement quantity, two different Portland cements (PC) and two different superplasticizer that the chemical nature is polycarboxylate and plynaphtalene, the aggregates used are (AG 3/8 mm, AG 8/15 mm), coarse and fine sand (SC, SF) witch fineness modulus 3.2 and 1 in the order. The dosage of the different superplasticizer used is chosen after experimental spreading tests of each self compacting concret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…S. Kennouche researched self-compacting concrete and found that the best workability results could be achieved when 15 % of silica fume was added to cement [11]. Badr El-Din Ezzat Hegazy made bricks for an extremely aggressive environment and found that the best physical and mechanical properties could be achieved and when the mixture contained 25 % (by weight) of silica fume [12].…”
Section: Introductionmentioning
confidence: 99%
“…S. Kennouche researched self-compacting concrete and found that the best workability results could be achieved when 15 % of silica fume was added to cement [11]. Badr El-Din Ezzat Hegazy made bricks for an extremely aggressive environment and found that the best physical and mechanical properties could be achieved and when the mixture contained 25 % (by weight) of silica fume [12].…”
Section: Introductionmentioning
confidence: 99%